Hubungan Psychosocial Care Perawat Dengan Kecemasan Pasien di Ruang Rawat Inap Dewasa RSUD Dr. H. Abdul Moeloek Provinsi Lampung - Elasari, Yunina; Brinka, Belli; Agustriyani, Feri; Wahyudi, Dian Arif (Journal of Nursing Invention, 2023)
Background: Anxiety is one of the primary indicators of the quality of health services in hospitals. It often occurs in hospitalized patients. Data from WHO in 2016 shows that about 3.6% of the entire population in the world is experiencing mental anxiety disorders. Psychosocial nursing care, which is psychological and social care, can reduce the anxiety level of inpatients. Objective: The study aimed to determine the correlation between psychosocial nursing care with patient anxiety in the adult inpatient room at the Regional Public Hospital of Dr.H Abdul Moeloek in Lampung Province. Method: The research design employed in this study was descriptive correlation utilizing a cross-sectional method. The population in this study was 112 patients in the adult inpatient rooms at the Regional Public Hospital of Dr.H Abdul Moeloek in Lampung Province, with samples of 100 people Result: The bivariate analysis in this research is conducted using the Chi-Square test. The research findings obtained p-value= 0.000, showing a significant relationship between psychosocial nursing care and patient anxiety in adult inpatient rooms. Conclusion: Psychosocial nursing care encompasses the domains of empathy, support, and information fulfillment. The importance of nurses in providing complete and accurate information about the patient's health condition in the inpatient room in an effort to reduce patient anxiety.